Manajemen Perpustakaan Sekolah dalam Menumbuhkan Budaya Literasi (Studi Multi Situs di SMA Hang Tuah 2 dan SMA Hang Tuah 5 Sidoarjo) - Rifa Utmawati; Erny Roesminingsih; Sri Setyowati (LP. Ma'arif Janggan Magetan, 2024)
This research aims to describe the implementation of School Library Management in Fostering a Culture of Literacy of Students of SMA Hang Tuah 2 and SMA Hang Tuah 5 Sidoarjo. This is multi-site study and method used in this research is qualitative, by describing and describing the implementation of school library management that has been implemented in SMA Hang Tuah 2 and SMA Hang Tuah 5 which includes planning, organization, implementation, and supervision. In obtaining the results of research and data, researches use interview and observation techniques. Then the data is analyzed in such a way, so that it becomes a qualitative research. The discussion and description of the data it has been done, this research concluded that the management carried out in the school library of SMA Hang Tuah 2 and SMA Hang Tuah 5 Sidoarjo has carried out the planning, organization, implementation, supervision, and evaluation process carried out by the principal, educators, and librarians. Thus, the School Literacy Movement program will be carried out and the process of fostering the literacy culture of students of SMA Hang Tuah 2 and SMA Hang Tuah 5 Sidoarjo begins to run as expected